2022
DOI: 10.1111/jdi.13863
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of umbilical cord serum miRNAs associated with childhood obesity: A pilot study from a birth cohort study

Abstract: We investigated umbilical cord serum microRNA (miRNA) profiles to identify biomarkers of a risk for obesity later in life. Participating children were divided into high-and low-risk groups of obesity based on the timing of adiposity rebound and the body mass index (BMI) at 5 years and randomly selected from each group for this study. 3D-Gene ® Human miRNA Oligo Chip was performed using cord serum in five children of both groups. The most relevant miRNAs were confirmed in 33 children of the groups using the Taq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…None of the studies involving the aforementioned screened miRNAs have been reported in the PCOS field. It should be noted that miR-130a-3p levels are higher in children at high risk of obesity than in those at low risk [21] . Hence, it is thought that these 11 miRNAs might be potential targets for PCOS study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies involving the aforementioned screened miRNAs have been reported in the PCOS field. It should be noted that miR-130a-3p levels are higher in children at high risk of obesity than in those at low risk [21] . Hence, it is thought that these 11 miRNAs might be potential targets for PCOS study in the future.…”
Section: Discussionmentioning
confidence: 99%